2013
DOI: 10.1371/journal.pone.0054493
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Ras Homologous C (RhoC) Induces Malignant Transformation of Hepatocytes In Vitro and in Nude Mouse Xenografts

Abstract: Ras homologous C (RhoC) is expressed in various cancers, including hepatocellular carcinoma (HCC). In this study, we first analyzed RhoC expression in 46 HCC tissue specimens and found that RhoC expression was significantly increased in HCC tissues compared to the adjacent normal liver tissues. Next, we investigated the role of RhoC in malignant transformation of normal hepatocytes. The HL7702 cell line was stably transfected with a RhoC expression vector and then subjected to cell proliferation, differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The aforementioned observations prompted us to investigate moreover the average migration of non-infected and infected U373MG depleted one of the three Rho isoforms cells, with RhoB and RhoC knockdown cells having the faster healing rate and in accordance with studies highlighting the role of these GTPases mainly in malignant transformation and to a less extend in motility [75], whereas the movement of RhoA silenced cells is decreased (Fig. 6A and 6B), revealing once more the differential role of RhoA, RhoB and RhoC in migration and invasion [76][77][78].…”
Section: Discussionmentioning
confidence: 65%
“…The aforementioned observations prompted us to investigate moreover the average migration of non-infected and infected U373MG depleted one of the three Rho isoforms cells, with RhoB and RhoC knockdown cells having the faster healing rate and in accordance with studies highlighting the role of these GTPases mainly in malignant transformation and to a less extend in motility [75], whereas the movement of RhoA silenced cells is decreased (Fig. 6A and 6B), revealing once more the differential role of RhoA, RhoB and RhoC in migration and invasion [76][77][78].…”
Section: Discussionmentioning
confidence: 65%
“…To date, the molecular mechanisms by which RHOC promote tumor development and metastasis are not fully understood (26). Previous studies have demonstrated that RHOC promote cancer progression by regulating the expression of MMP genes (14,23,27). It is well established that MMPs induce cancer cell invasion and metastatic spread by degrading the extracellular matrix and other barriers (28).…”
Section: Discussionmentioning
confidence: 99%
“…RhoC was shown to induce angiogenesis by regulating endothelial cell migration and organization, 41 and to maintain vascular homeostasis by modulating the endothelial cell proliferation and permeability 42 . In addition, reports have shown that RhoC increases the VEGF expression 40,50‐52 . It was reported that p38 is involved in RhoC‐induced VEGF production in breast cancer cells 52 .…”
Section: Discussionmentioning
confidence: 99%